Study on the Zero-Backlash Roller Enveloping Precision Reducer - Deng, Xingqiao; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book aims to describe the basis meshing theory of roller enveloping worm gear and provides the new design and manufacturing method for solving the problem of backlash in gearing transmission. Also, it presents a new efficient numerical calculation means to predict the lubrication properties for two complex surface meshing in space. Our results provide a series of new viewpoints for design precision reducer. .
Introduction -- Theory of Zero Backlash High Precision Roller Enveloping Reducer -- Parametric Study of Meshing Characteristics with Respect to Different Meshing Rollers -- Mathematical Calculation and Finite Element Analysis -- Optimal Design -- Manufacturing and Experiment -- Conclusion.
Keywords: Machinery; Engineering mathematics; Mathematics$1 (BData processing.s; Machinery and Machine Elements; Engineering Mathematics; Computational Science and Engineering; Gearing, Reduction; Roller bearings